A New Dynamic Modelling Algorithm for Pneumatic Muscle Actuators - Cao, Jinghui; Xie, Sheng Quan; Zhang, Mingming; Das, Raj (Intelligent Robotics and Applications, 2014)
Pneumatic muscle actuators (PMAs) have been widely used in wearable robots due to its high power to weight ratio and intrinsic compliance. However, dynamic modelling of PMAs, which is important to control performance, has not been researched extensively. Hence, a testing device was designed and built to investigate PMA’s dynamics. The device automates the experimental process by providing motions and recording pressure, force, position and velocity data. The gathered experimental data enable the authors to validate a previous PMA dynamic model. Meanwhile, new models are developed from the original model. Statistical analysis proves that the new models can better represent the PMA dynamics during the experiments.